The optimal true-ileal-digestible lysine and total sulfur amino acid requirement for nursery pigs between 20 and 50 lb - Schneider, J.D.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
An experiment was conducted with 360 pigs (PIC, avg BW = 22.7 lb) to determine the appropriate true-ileal-digestible (TID) lysine and total sulfur amino acid (TSAA) requirement of nursery pigs, and consequently to determine the optimal TSAA-to-lysine ratio. This trial was organized as a combination of two simultaneous experiments, with one set of diets consisting of five treatments with increasing TID lysine (0.9, 1.0, 1.1, 1.2, and 1.3%) and the second set of diets consisting of five treatments with increasing TID TSAA (0.56, 0.62, 0.68, 0.74, and 0.81%). The highest concentrations of both lysine and TSAA (1.3% and 0.81%, respectively) were combined as one diet and used in both the lysine and TSAA titrations, to give a total of 10 treatments. Pigs were randomly allotted to eight replications with five pigs per pen, on the basis of BW. Average daily gain increased (linear, P<0.01), but ADFI decreased (linear, P<0.06) with increasing TID lysine. Increasing TID lysine also improved (linear, P<0.01; and quadratic P<0.05) F/G. Increasing TID TSAA from 0.56 to 0.81% increased (linear, P<0.02) ADG and improved (linear, P<0.01) F/G. The arrangement of treatments in this experiment determined both the lysine and TSAA requirements simultaneously, which allowed the use of a regression approach in the establishment of a TID TSAA-to-lysine ratio. In this approach, ADG and F/G values are plotted as the dependent variables on the X axis and the TID lysine and TSAA concentrations are plotted on the Y axis. A trend line is fit through the data to develop a regression equation to predict the TID lysine and TSAA requirements, which can be used to estimate the TID TSAA-to-lysine ratio. The values for ADG and F/G from the individual lysine and TSAA trials must overlap to allow this approach to work. Regression analysis of the response surface resulted in an estimated TID TSAA-to-lysine ratio range of 55 to 61% for ADG and 57 to 61% for F/G.
Keywords: Lysine; TSAA; Nursery pigs; Pigs; Swine